Adherence to iron supplementation and associated factors among pregnant women in Cambodia: Insights from the 2021–2022 Demographic and Health Survey - Buanasita, Annas; Sumarmi, Sri; Mahmudiono, Trias; Melaniani, Soenarnatalina; Salim, Lutfi A.; Sokvy, Ma; Sari, Nur MW. (Narra J, 2025)
Iron deficiency is the leading cause of anemia during pregnancy, a major public health concern in many developing countries. To mitigate anemia, iron supplementation for at least 90 days is recommended for pregnant women. The aim of this study was to evaluate adherence to iron supplementation during pregnancy and to identify its key determinants in Cambodia. A cross-sectional study was conducted using secondary data from the 2021–2022 Cambodia National Demographic and Health Survey. Key variables assessed included maternal age, education level, ethnicity, wealth index, number of pregnancies, age at first pregnancy, prenatal care provider, timing of the first antenatal care (ANC) visit, and frequency of ANC visits. Multivariate logistic regression was employed to evaluate associations between adherence and independent variables. A total of 4,475 women aged 15–49 years who had been pregnant in the past five years were included in the analysis, with 91.2% adhering to iron supplementation for at least 90 days. Multivariate logistic regression showed that those with primary and higher education had greater odds of adherence (odds ratio (OR)=1.38; 95%CI: 1.00–1.90; OR=3.07; 95%CI: 1.39–6.79, respectively) compared to women with no education. There was a positive relationship between education level and adherence. Women who attended four or more ANC visits were more likely to adhere (OR=2.93; 95%CI: 2.27–3.77), and those who initiated ANC in the first trimester had higher adherence compared to those who started later (OR=1.78; 95%CI: 1.35–2.36). This study highlights that education level, frequency, and timing of ANC visits significantly influenced adherence to iron supplementation. Strengthening maternal education and promoting early and regular ANC follow-up should be prioritized to improve adherence and prevent anemia during pregnancy.